What is beautiful is good - Hatfield, Elaine; Dion, Karen; Bercheid, Ellen (1972)
Examined whether physically attractive stimulus persons, both male and female, are (a) assumed to possess more socially desirable personality traits than physically unattractive stimulus persons, and (b) expected to lead better lives (e.g., be more competent husbands and wives and more successful occupationally) than unattractive stimulus persons. Sex of Subject * Sex of Stimulus Person interactions along these dimensions also were investigated. Results with 30 male and 30 female undergraduates indicate a "what is beautiful is good" stereotype along the physical attractiveness dimension with no Sex of Judge * Sex of Stimulus interaction. Implications of such a stereotype on self-concept development and the course of social interaction are discussed.